Relationship of Leadership and Work Environment with Work Satisfaction of Health Personnel at dr. (H.C) Ir. Soekarno Bangka Belitung Islands Province - Nazilah Nazilah; Kgs. M. Sobri; Alfitri Alfitri (Jurnal Mantik, 2021)
The relation between the leadership and work environment so that job satisfaction can be achieved. This study aims to examine the relationship and influence between leadership and job satisfaction, Relationship and influence between the environment and job satisfaction of Health Workers at The Regional General Hospital Dr. (H.C) Ir. Soekarno, Bangka Belitung Province. The research method used is descriptive quantitative. The results showed that is leadership of the hospital director has a strategic role in creating job satisfaction. Similarly, the work environment also has an important role in creating a feeling of comfort and safety so that in the end it creates job satisfaction for health workers at the Dr. (H.C) Ir. Soekarno, Bangka Belitung Province. This shows that existing work environment has a positive and significant effect on the performance of health workers. The creation of a positive relationship between leadership and work environment on job satisfaction cannot be separated from the influence of the situational leadership style carried out by the Hospital Director. In the daily work environment, The Director always provides guidance and direction, and provides socio-emotional support for Health Workers. This condition certainly shows the dynamic leadership style of a hospital director, so as to create a safe and comfortable work environment. Through this study, it can be concluded that leadership in health institutions has a strategic role in creating job satisfaction. Likewise, the work environment has an important role in creating a feeling of comfort, safety, and peace for health workers. In addition, there is also a close relationship between leadership and job satisfaction for Health Workers at the Dr. (H.C) Ir. Soekarno, Bangka Belitung Province.